(untitled) - Nist-Olejnik, Sherrie (Berkeley, 2016)
This updated classic gives students the tools they need to successfully transition from high school to college, avoid rookie mistakes, and set themselves up for academic success from day one
Keywords: Định hướng sinh viên đại học,College student orientation; Hoa Kỳ,United States